The Evolution of the Chilean-Argentinean Andes (Springer Earth System Sciences,, 2018)
This book describes the Mesozoic to Cenozoic evolution of the Chilean and Argentinean Andes. The book is structured from a historical perspective concentrating on specific processes explained in each chapter. The chapters cover dynamic subsidence; neotectonics; magmatism; long and short term deformation; spatial development of ancient orogenic processes that control Andean reactivations; relation between ocean bathymetry and deformation. Sources of detritus through Andean construction are discussed by specialists from both sides of the Southern Andes. This book provides up-to-date reviews, maps, evolutionary schemes and extensive reference lists useful for geoscientists and students in Earth Science fields.